Gambaran Ekstrakurikuler di Taman Kanak-kanak Telkom School Padang - Nurhasanah, Septria; Yeni, Indra (Indonesian Journal of Islamic Early Childhood Education, 2019)
This study aims to describe extracurricular activities at the Telkom School Kindergarten in Padang. This research uses descriptive method using qualitative. Informants from this study were principals, class teachers and extracurricular teachers. Data collection techniques in this study used observation techniques, interview techniques and documentation techniques. Data analysis techniques used are data triangulation techniques. There are five extracurricular activities carried out namely hafidz extracurricular activities, dancing, swimming, computer, and marching bands. The result of the study are generally known that extracurricular activities at the Padang School Kindergarten in Padang have been ongoing. The teacher has carried out planning, implementation, and evaluation that is able to develop talents and channel children?s interests trough scheduled activities even though there are still shortcomings in their implementation.